MicroRNA-146b Promotes Myogenic Differentiation and Modulates Multiple Gene Targets in Muscle Cells - Khanna, Nidhi (Public Library of Science, 2014)
MicroRNAs are established as crucial modulators of skeletal myogenesis, but our knowledge about their identity and targets remains limited. In this study, we have identified microRNA-146b (miR-146b) as a novel regulator of skeletal myoblast differentiation. Following up on a previous microRNA profiling study, we establish that the expression of miR-146b is up-regulated during myoblast differentiation in vitro and muscle regeneration in vivo. Inhibition of miR-146b led to reduced myoblast differentiation, whereas overexpression of miR-146b enhanced differentiation. Computational prediction combined with gene expression information has revealed candidates for miR-146b targets in muscles. Among them, the expression of Smad4, Notch1, and Hmga2 are significantly suppressed by miR-146b overexpression in myocytes. In addition, expression levels of Smad4, Notch1 and Hmga2 are decreased during myoblast differentiation and muscle regeneration, inversely correlating to the levels of miR-146b. Importantly, inhibition of endogenous miR-146b prevents the down-regulation of Smad4, Notch1 and Hmga2 during differentiation. Furthermore, miR-146b directly targets the microRNA response elements (MREs) in the 3′UTR of those genes as assessed by reporter assays. Reporters with the seed regions of MREs mutated are insensitive to miR-146b, further confirming the specificity of targeting. In conclusion, miR-146b is a positive regulator of myogenic differentiation, possibly acting through multiple targets.